Bipolar Disorder in the Character of Kat Baker Reflected in Spinning Out (2020) of 10 Episodes - Sukirman Sukirman; Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
This study is aimed to analyse: (1) the symptoms of bipolar disorder as reflected in the main character of Spinning Out (2020) series, and (2) the mental condition of the main character as a bipolar sufferer reflected in the Spinning Out (2020) series. The researcher uses the qualitative method to examine the problem. The object of this study is the character Kat Baker in the Spinning Out (2020) series. The data used in this study is collected by the researcher through some steps, namely watching and reading, identifying, classifying, and selecting. In order to answer the problem statement and draw a conclusion from this study, the selected data is analyzed by the researcher through some steps, namely displaying, explaining, and interpreting. The approach and theory that the researcher uses to analyze the problem is psychology of literature and psychoanalysis. The result of this study shows that (1) the symptoms of bipolar disorder as reflected in the main character of Spinning Out (2020) series are depicted through various characteristics that occur in depressive and manic episode, anxiety, low self-esteem, libido issues, and self-harm; and (2) the mental condition of the main character as a bipolar sufferer makes her become an impulsive and overprotective person.